Lovastatin production by Aspergillus fischeri under solid state fermentation from coconut oil cake - Latha, Parvatham Madhu; Chanakya, Pallem; Srikanth, Manipati (Nepal Journal of Biotechnology, 2012)
The main aim of the present investigation was to optimize the fermentation parameters that enhance the maximum production of lovastatin by Aspergillus fischeri using coconut oil cake as the solid substrate under solid state fermentation. The maximum yield of lovastatin (14.77 mg/g dry substrate) using coconut oil cake as the substrate was achieved with the following optimized process parameters: fermentation time (7 days), initial moisture content (60% v/w), inoculum volume (2ml of five day old culture), initial pH (5.0), incubation temperature (30ºC), lactose (1% w/v) and malt extract (1% w/v). Keywords: Lovastatin; Aspergillus fischeri; Coconut oil cake; Fermentation parameters; Optimization DOI: http://dx.doi.org/10.3126/njb.v2i1.5641 Nepal Journal of Biotechnology Jan.2012, Vol.2(1): 26-36